The Relationship of Pain and Nausea in Postoperative Patients for 1 Week After Ambulatory Surgery. Issue 10 (October 2015) - Odom-Forren, Jan; Rayens, Mary K.; Gokun, Yevgeniya; Jalota, Leena; Radke, Oliver; Hooper, Vallire; Wiggins, Amanda T.; Apfel, Christian C.
Abstract : Objectives: The purpose of this study was to determine if pain level was associated with demographic or surgery-specific characteristics among patients recovering from ambulatory surgery; and to assess the relationship between pain level and nausea over the 7-day postoperative period, controlling for demographic and surgery-related covariates. Materials and Methods: This longitudinal study assessed the pain and nausea of 248 eligible patients during the day of surgery (DOS) and the 7 days following ambulatory surgery. Postoperative data were assessed using standardized questions about severity of pain and nausea symptoms. Participants who had a cumulative pain score of ≥24 over the 8-day period were categorized as having high pain. Repeated-measures analysis of variance was used to assess differences in nausea by pain group over time, controlling for demographic, surgical variables, and antiemetic and analgesic use. Results: There were significant differences between 2 pain groups in age, surgical procedure, cumulative morphine equivalent dose, and use of antiemetics postdischarge. The longitudinal analysis demonstrated that patients in the high-pain group reported a greater degree of nausea on DOS and on each of the first 5 days postsurgery, controlling for differences in age, sex, education, use of antiemetics presurgery and postsurgery, use of acetaminophen postsurgery, daily morphine equivalent dose, and surgical procedure. Discussion: Younger patients and those receiving orthopedic procedures may be at greatest risk for postoperative pain. Patients with high pain reported a significantly greater degree of nausea on DOS through the first 5 days postdischarge. As the majority of surgeries are now conducted in the ambulatory setting, it is imperative that we determine pain management regimens and patient education practices that will allow for a more comfortable recovery for our patients.